Upaya Menyelamatkan Pemilihan Umum Di Tahun 2020 - Andrian Habibi (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:The continuation of the 2020 general election in political view is seen as a spring in the dry season of the Covid-19 pandemic uncertainty. Therefore, the holding of elections answers all political endeavors of regional head candidates. Political communication efforts before the Covid-19 Pandemic will be answered automatically. Thus, prospective election participants can reduce excess expenditure during a pandemic, because the political competition budget does not reach a maximum surplus.Keywords: General Election, Covid-19 Abstrak:Keberlangsungan pemilihan umum 2020 dalam pandangan politik dianggap bagaikan mata air di kemarau ketidakpastian pandemi Covid-19. Karenanya, penyelenggaraan pemilihan menjawab semua ikhtiar politik dari para calon kepala daerah. Usaha komunikasi politik sebelum Pandemi Covid-19 akan terjawab dengan sendirinya. Dengan demikian, calon peserta pemilihan bisa mengurangi pengeluaran yang berlebih saat pandemi, karena anggaran kompetisi politik tidak mencapai surplus maksimal.Kata Kunci: Pemihan Umum, Covid-19